Cambios en el uso de la tierra, urbanización y recurso hídrico. Transformaciones del espacio costero de El Coco, Guanacaste, Costa Rica - Orias Arguedas, Lidia (2016)
This article studies the coastline El Coco, in Nicoya Peninsula located in Guanacaste, Costa Rica. The study is about the aquifer El Coco, in Carrillo, in which the use of land shows some changes such a rapid urban growth due to tourism, a signifcant pressure for water resource, an a non-regulated use of water wells in hands of private domain. To understand this situation an interpretation from geographical perspective is necessary in order to explain some socio-historical transformations in the province, and highlight the conditions and factors associated with the problem of –land– intensive use, uncontrolled exploitation and high risk of water resources pollution.